Matrix resistance toward proteolytic cleavage controls contractility‐dependent migration modes during angiogenic sprouting - Weiß, Martin S.; Trapani, Giuseppe; Long, Hongyan; Trappmann, Britta (Technische Universität Dortmund, 2024)
Tissue homeostasis and disease states rely on the formation of new blood vessels through angiogenic sprouting, which is tightly regulated by the properties of the surrounding extracellular matrix. While physical cues, such as matrix stiffness or degradability, have evolved as major regulators of cell function in tissue microenvironments, it remains unknown whether and how physical cues regulate endothelial cell migration during angiogenesis. To investigate this, a biomimetic model of angiogenic sprouting inside a tunable synthetic hydrogel is created. It is shown that endothelial cells sense the resistance of the surrounding matrix toward proteolytic cleavage and respond by adjusting their migration phenotype. The resistance cells encounter is impacted by the number of covalent matrix crosslinks, crosslink degradability, and the proteolytic activity of cells. When matrix resistance is high, cells switch from a collective to an actomyosin contractility-dependent single cellular migration mode. This switch in collectivity is accompanied by a major reorganization of the actin cytoskeleton, where stress fibers are no longer visible, and F-actin aggregates in large punctate clusters. Matrix resistance is identified as a previously unknown regulator of angiogenic sprouting and, thus, provides a mechanism by which the physical properties of the matrix impact cell migration modes through cytoskeletal remodeling.
Advanced science;19(11)
Keywords: angiogenesis; cell migration; cell-ECM interactions; organ-on-chip; synthetic hydrogels; 540